2010
DOI: 10.1590/s0104-42302010000600020
|View full text |Cite
|
Sign up to set email alerts
|

Formação e experiência profissional dos médicos prescritores de antirretrovirais no Estado de São Paulo

Abstract: results. Regular ARV prescriptions were issued to 74 thousand patients by 1,609 physicians whose characteristics were as follows: even gender distribution, age 30 to 49 years, living in the metropolitan area of Greater São Paulo, graduated an average of 16.1 years ago at 93 different Brazilian medical schools, holding specialty diplomas in 67.5% of cases, most in the field of Infectious Diseases (38.9%). The mean number of patients per physician was 10, although 51.6% of physicians prescribed for 20 or more pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 12 publications
0
4
0
Order By: Relevance
“…However, this is not what actually occurred, considering that the rate of drug interactions was high. Investigation found that 32.5% of physicians who prescribed ART lacked any kind of specialization, something that may influence the occurrence of DDI 16 .…”
Section: Discussionmentioning
confidence: 99%
“…However, this is not what actually occurred, considering that the rate of drug interactions was high. Investigation found that 32.5% of physicians who prescribed ART lacked any kind of specialization, something that may influence the occurrence of DDI 16 .…”
Section: Discussionmentioning
confidence: 99%
“…25 In Brazil, a similar study conducted in São Paulo showed that 51.2% of PPAT were formally trained IDs; if IDs who were formally certified by the BSID were added, 67.2% of Brazilian PPAR fell into this category. 28 …”
Section: Discussionmentioning
confidence: 99%
“…No such influence was detected. An analysis of the professional profile of physicians who prescribe antiretroviral drugs to HIV infected persons in the State of São Paulo led Scheffer et al66 to conclude that the absolute majority of HIV patients receive their prescriptions from duly trained and experienced physicians. Nevertheless, the large number of non-qualified physicians together with the reduced number of physicians in HIV high incidence regions make up the major challenge for comprehensive and adequate care of HIV patients.…”
Section: Reviewmentioning
confidence: 99%